Application of Legal Considerations for Judges with Visum Et Repertum Evidence in the Criminal Act of Preplanned Murder Analysis of Decision Number 1100/Pid.B/2024/Pn Mdn - Eman Triboi Waruwu; Yusuf Hanafi Pasaribu; Winta Hayati (SEAN Institute, 2026)
Visum Et Repertum is a written report from a doctor (expert) made under oath, regarding what was seen and found on living evidence, corpses or physical or other evidence then carried out an examination based on the best knowledge. This study aims to analyze the regulation of the position of visum et repertum as evidence in criminal cases in Indonesia, and the application of legal considerations for judges with visum et repertum evidence in premeditated murder crimes. The research method used is normative juridical with a case and legislation approach and uses various secondary data such as regulations, legislation, court decisions, legal theory doctrines and can also be in the form of opinions of scholars and analyzed qualitatively. The results of the stu dy conclude that the regulation of the position of visum et repertum as evidence in criminal cases in Indonesia is not explicitly regulated in the Criminal Procedure Code. However, in Staatsblad 1937 Number 350 in article 1 it is stated that visum et repertum is a written statement made by a doctor under oath or promise about what is seen on the object being examined which has the power of evidence in criminal cases referring to article 184 paragraph (1) point c of the Criminal Procedure Code regarding written evidence. The application of legal considerations for judges with visum et repertum evidence in the crime of premeditated murder in decision Number 1100 / Pid.B / 2024 / PN Mdn, has applied legal considerations with visum et repertum evidence that has been issued by the Department of Forensic Medicine and Medicolegal Sciences, Bhayangkara Hospital TK II Medan Number: 19 / III / 2024 / RS. Bhayangkara dated March 24, 2024. The conclusion of the study confirms that judges in their decisions prioritize facts in court that are in accordance with the values of justice, certainty, and legal benefits.